Equivalence of velocity-level and acceleration-level redundancy-resolution of manipulators - Cai, Binghuang; Zhang, Yunong (Physics letters. A, 2009)
The equivalence of velocity-level and acceleration-level redundancy resolution of robot manipulators is investigated in this Letter. Theoretical analysis based on gradient-descent method and computer simulations based on PUMA560 robot manipulator both demonstrate the equivalence of redundancy-resolution schemes at different levels.